Paralytic Shellfish Toxins in Alaskan Butter Clams: Does Cleaning Make Them Safe to Eat? - R. Wayne Litaker; Julie A. Matweyou; Steven R. Kibler; D. Ransom Hardison; William C. Holland; Patricia A. Tester (Toxins)
Butter clams (Saxidomus gigantea) are a staple in the subsistence diets of Alaskan Native communities and are also harvested recreationally. This filter–feeding species can accumulate saxitoxins (STXs), potent neurotoxins produced by late spring and summer blooms of the microalga Alexandrium catenella. The consumption of tainted clams can cause paralytic shellfish poisoning (PSP). Traditional beliefs and early reports on the efficacy of removing clam siphons have created the impression that cleaning butter clams by removing certain tissues makes them safe to eat. However, the toxin distribution within clams can vary over time, making the practice of cleaning butter clams unreliable. This study tested the effectiveness of the cleaning methods practiced by harvesters on Kodiak Island, Alaska. Specifically, butter clams were cleaned by removing different tissues to produce samples of “edible” tissues that were tested for STX content. The results were compared to historical data from a study conducted in Southeast Alaska from 1948 to 1949. Using these data, the risk for an average–sized man and woman consuming 200 g of edible tissue was calculated. The results showed that for clams containing >200 µg STX–equivalents 100 g edible tissue−1, no cleaning method reduced the concentration of STXs in the remaining tissue below the regulatory limit. Meals containing >900 µg STX–equivalents 100 g edible tissue−1 posed a substantial risk of moderate or severe symptoms. No cleaning method assured that untested butter clams are safe to eat.